2022
DOI: 10.1007/s12079-022-00713-y
|View full text |Cite
|
Sign up to set email alerts
|

CCN2/CTGF promotes liver fibrosis through crosstalk with the Slit2/Robo signaling

Abstract: Liver fibrosis is the common outcome of many chronic liver diseases, resulting from altered cell-cell and cell-matrix interactions that promote hepatic stellate cell (HSC) activation and excessive matrix production. This study aimed to investigate functions of cellular communication network factor 2 (CCN2)/Connective tissue growth factor (CTGF), an extracellular signaling modulator of the CYR61/CTGF/Nov (CCN) family, in liver fibrosis. Tamoxifen-inducible conditional knockouts in mice and hepatocyte-specific d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In addition, the overexpression of CCN5 resulted in basal higher but reduced induction of CCN2 by TGF‐β1 (Fig. 4), which represents a CCN protein that evolves profound fibrotic activities (Gressner et al 2009; Weiskirchen 2011; Ramazani et al 2018; Pi et al 2022).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the overexpression of CCN5 resulted in basal higher but reduced induction of CCN2 by TGF‐β1 (Fig. 4), which represents a CCN protein that evolves profound fibrotic activities (Gressner et al 2009; Weiskirchen 2011; Ramazani et al 2018; Pi et al 2022).…”
Section: Discussionmentioning
confidence: 95%
“…In particular, CCN2 is increasingly expressed in activated HSC, which directly promotes the expression of extracellular matrix proteins. A recent study has shown that conditional knockout in mice and hepatocyte‐specific deletion of CCN2 in rats resulted in reduced expression of fibrosis‐related genes including Slit, α‐SMA, and collagen type I when subjected to peri‐central hepatocyte damage caused by carbon tetrachloride intoxication (Pi et al 2022). On the contrary, CCN1 is upregulated during hepatic injury acting as an inhibitor of liver fibrosis by triggering induction of reactive oxygen species, cellular senescence, apoptosis and reduced TGF‐β signaling in activated HSC and portal fibroblasts (Kim et al 2013; Borkham‐Kamphorst et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ccn1 may contribute to hepatic inflammation and affect ECM remodeling considering its effects on macrophage recruitment and HSC apoptosis (Bai et al 2010; Borkham‐Kamphorst et al 2016). Unlike Ccn1, which is highly induced in HSC, Ccn2 is accumulated in periportal Hnf4α + hepatocytes within hours post CCl 4 intoxication and this accumulation can be enhanced in regenerating murine livers that receive 2% alcohol exposure (Zhou et al 2020; Pi et al 2023). Ccn2 induction is associated with Hnf4α decline, nuclear Yap accumulation, and Tgfβ upregulation during the early stages of liver regeneration following PHx or ethanol/CCl 4 ‐induced liver injury in mice (Zhou et al 2020).…”
Section: Ccns In Hepatocyte‐driven Liver Regenerationmentioning
confidence: 99%
“…Overexpression of this molecule enhances the susceptibility of the liver to other fibrotic stimuli (Tong et al 2009). Conversely, deletion of this gene in conditional knockouts reduces fibrotic responses after chronic liver injury caused by CCl 4 (Pi et al 2023). In addition, Ccn2 can be secreted as profibrotic signals in extracellular vesicles to promote tissue fibrosis (Brigstock 2021).…”
Section: Ccns In Hepatocyte‐driven Liver Regenerationmentioning
confidence: 99%
“…The matricellular protein cellular communication network-2 (CCN2/CTGF) is a fibrogenic cytokine that has been identified as a downstream mediator of profibrogenic factors in human biopsies of various fibrotic organ pathologies as well as in experimental models of fibrotic disorders. In kidney fibrosis, CCN2 overexpression is associated with cellular proliferation and excessive accumulation of ECM in both glomerular and tubulointerstitial areas . The central role of CCN2 in the development of kidney fibrosis has also been demonstrated in several in vitro experiments using different renal cell types. , Furthermore, inhibition of endogenous CCN2 using monoclonal antibodies, antisense oligonucleotides, or gene silencing has shown promise in treating experimental renal diseases, including folic acid-induced renal injury, unilateral ureteral obstruction (UUO), and diabetic nephropathy. , …”
Section: Introductionmentioning
confidence: 99%